Drugs targeting the NO-sGC-cGMP pathway in the treatment of patients with COPD-associated pulmonary hypertension: a systematic review - Alqarni, Abdullah A.; Alghamdi, Sara A.; Aldhahir, Abdulelah M.; Alqahtani, Jaber S.; Siraj, Rayan A.; Alasimi, Ahmed H.; Bintalib, Heba M.; AlGarni, Abdulkareem A.; Majrshi, Mansour; Alshabasy, Adel M.; AlBahrani, Salma; Alwafi, Hassan (Frontiers in Pharmacology, 2025)
BackgroundPulmonary hypertension (PH) due to chronic obstructive pulmonary disease (COPD) is categorized as group 3 PH and is associated with increased mortality and morbidity. Currently, there are no approved therapies for those who have PH secondary to COPD due to conflicting evidence. Therefore, this systematic review aims to summarize the current evidence on the effectiveness of drugs targeting the nitric oxide (NO)-soluble guanylate cyclase (sGC)-cyclic guanosine monophosphate (cGMP) pathway on clinical outcomes among patients with COPD-associated PH.MethodsWe conducted a comprehensive search of electronic databases, including Embase, Medline, Cochrane, and Scopus, from inception to 1 February 2024. Studies investigating the efficacy of drugs targeting the NO-sGC-cGMP pathway on clinical outcomes in patients with COPD-associated PH were included. Exclusion criteria encompassed case reports, systematic reviews, review articles, conference abstracts with no full text, non-full-text articles, non-English manuscripts, opinion articles, and book chapters. Two distinct Cochrane risk-of-bias tools designed for randomized and non-randomized clinical trials were used to evaluate the risk of bias within the selected studies for inclusion.ResultsFourteen studies, comprising a total of 567 adult patients diagnosed with PH secondary to COPD, met the inclusion criteria and were included in this systematic review. Among these, nine studies reported significant improvements in clinical parameters related to pulmonary hemodynamics. Improvement in exercise capacity was observed in four out of seven studies. Three studies evaluated dyspnea severity and quality of life following treatment with agents targeting the NO-sGC-cGMP pathway. Of these, three demonstrated improvement in dyspnea severity while two reported enhancements in health-related quality of life. Substantial heterogeneity was evident regarding the potential of pharmacological agents targeting the NO-sGC-cGMP pathway to enhance gas exchange, lung function, and arterial oxygenation in COPD patients with concurrent PH.ConclusionThe short-term use of oral drugs targeting the NO-sGC-cGMP pathway, particularly sildenafil, demonstrates promising potential for enhancing pulmonary hemodynamics, exercise capacity, dyspnea severity, and health-related quality of life but not lung function and oxygenation status in adult patients with COPD-associated PH. Further double-blind, randomized, placebo-controlled trials are needed to assess the therapeutic benefits of agents targeting the NO-sGC-cGMP pathway, particularly inhaled therapies for managing PH due to COPD.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/#recordDetails, CRD42023453503.